Relevance of Social Capital and Community Participation in The “Karya Sakti” BUMDES Program in Lubuk Sakti Indralaya - Konita Turania; Lishapsari Prihatini; Trecy Austin; Dita Mayriesta (Brawijaya University, 2022)
The Establishment of BUMDes is intended as a joinf effort between the village government, in order to developthe economic potential of the village and community welfare. This study is to analyse the effect of social capital on community Participation in Lubuk Sakti Village, IndralayaDistrict. The theory used is the theory of social capital proposed by Bourdie, Fukuyama, and Hasbullah. The Overall research time is from July to October 2021. The Population Characteristics are individuals aged 25-40 years in Lubuk Sakti Village. The sampling technique used is random sampling, the research sample is 117 respondents from 3 hamlets, 10% of each total population is taken. After the data is obtained, it is analyzed using the SPSS 25.00 software application. The results showed that there was a positive relationship between Social Capital and Community Participation in BUMDes. Then based on the SPSS 25 table,the 2 – tailed significant difference between the two variables.